495 A Retrospective Seven-Year Study on The Incidence of Cruise Ship Orthopaedic Injuries and Their Impact on A Major Trauma Centre (MTC). (4th May 2021) - Hayat, Z
Abstract: Introduction: Cruises have increased in popularity worldwide. Falls are the most common seafaring accident, a leading cause of morbidity and mortality. The aim of this, the first UK study, was to analyse the incidence of orthopaedic injuries sustained on cruise ships presenting to an MTC over a seven-year period. Method: A retrospective analysis of cruise injuries resulting in admission or ongoing follow up by the orthopaedic department was conducted. Demographic details, injuries sustained, management and length of stay were reviewed. Results: Over the seven-year period, 204 patients were identified, 29 a year on average. The median age was 74 with 70.6% female patients. Of the 221 injuries, 80.9% were fractures (n = 179); neck of femur fractures predominated (27.7%, ). There were 140 admissions with a total of 1250 days in hospital. Linear regression models showed the increasing number of admissions to be statistically significant (p < 0.05), as was the upward trend in the number of lower limb injuries (p < 0.05). Conclusions: The majority of injuries occur in elderly females, where fragility fractures are common. It is vital that cruise ships put measures in place to minimise the risk of such accidents occurring; we hope our findings can assist the formulation of such protocols.